Improved preparation method suitable for FIB analysis of section of low-melting-point material

By sputtering a platinum layer on the surface of the FIB analysis test piece and coating a polymer layer with high thermal conductivity, the problem of low melting point material migration in FIB cutting analysis is solved, and the analysis quality and test piece stability are improved.

CN119843227APending Publication Date: 2025-04-18NANJING FANQUAN ELECTRONIC TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411879475.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

During the FIB cutting analysis process, low-melting point materials cause metal migration due to rising temperature, destroying the original structure, and affecting the analysis quality.

Method used

The first platinum layer is sputtered on the surface of the semiconductor test piece, and a polymer layer with a preferred thermal conductivity is coated thereon, with a thickness of 300-1000 nm, and then the second and third platinum layers are prepared on the polymer layer.

Benefits of technology

By adding polymer layer, the heat during FIB cutting analysis can be effectively derived, the migration of low-melting point metals is reduced, the analysis quality is improved, the cut marks are reduced, and the stability of the test piece is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119843227A_ABST
    Figure CN119843227A_ABST
Patent Text Reader

Abstract

The invention provides an improved preparation method suitable for FIB analysis of a section of a low-melting-point material. The improved preparation method comprises the following steps: S1, preparing a semiconductor test piece; the semiconductor test piece comprises a target area; s2, sputtering a first platinum layer on the upper surface of the semiconductor test piece; s3, coating the first platinum layer with a polymer layer; the thickness of the polymer layer is 300 to 1000 nm; s4, preparing a second platinum layer on the upper surface of the polymer layer; s5, preparing a third platinum layer on the upper surface of the second platinum layer; the high-molecular layer with better heat conduction is additionally arranged above the target area and between the first platinum layer and the second platinum layer, so that heat accumulated during FIB cutting analysis is effectively guided out of the target area, the opportunity of outward migration of low-melting-point metal is reduced, meanwhile, preparation is convenient, implementation can be carried out at room temperature in a simple coating mode, and the cost is low. The high polymer material does not react with composition elements in the test piece, and the damage and tool mark effect of the test piece caused by high-energy ion beam bombardment can be relieved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of semiconductor test piece preparation methods, and in particular to an improved preparation method suitable for FIB analysis of cross sections of low-melting-point materials. Background Art

[0002] The preparation method for FIB analysis is usually used in the fields of semiconductors, materials science and biology. It uses a focused ion beam to accurately cut, etch or engrave samples for micro-processing and observation of samples. Figure 1 As shown, a first platinum (Pt) layer is firstly prepared by sputtering on the surface of the test piece, and then two platinum layers (the second and third platinum layers) are prepared above the analysis target area in the FIB chamber by using an electron beam and an ion beam respectively. Finally, the FIB is used for cutting to obtain the cross-sectional structural information of the test piece.

[0003] However, during the FIB cutting process, due to the continuous bombardment of high-energy ions, if the thermal conductivity of the material near the target area is not good, heat will accumulate, causing local temperature rise. This does not cause problems for materials with high melting points (such as Si, Cu, Ge) generally used in semiconductor processes, but in compound semiconductors (InGaN, InGaP... and other light-emitting diodes) or solar cells (copper indium gallium selenide) containing metals with low melting points, such as indium (In, melting point is 156.6 ℃), when FIB cutting is used for analysis, the temperature rise in the target area causes the migration of low-melting-point metals, resulting in the destruction of the original structure, causing great trouble in analysis. It is a common phenomenon that the effect of atomic migration occurs due to temperature increase, so finding a method to effectively reduce the temperature of the working area is an urgent task in the industry. Summary of the invention

[0004] The purpose of the present invention is to solve the shortcomings of the prior art and to propose an improved preparation method suitable for cross-sectional FIB analysis of low-melting-point materials, which effectively improves the quality of cross-sectional FIB analysis in material analysis. By introducing an added polymer layer, a better solution is provided for low-melting-point materials that were originally unable to be accurately analyzed. Compared with the existing analysis technology, the present invention has at least two advantages. One is that the low-melting-point metal no longer migrates during FIB cutting analysis, and the other is that the tool marks are reduced, thereby improving the quality of FIB analysis.

[0005] To achieve the above object, the present invention adopts the following technical solutions: An improved preparation method suitable for FIB analysis of cross-sections of low-melting-point materials comprises the following steps: S1: prepare a semiconductor test piece; The semiconductor test piece includes a target area; S2: sputtering a first platinum layer on the upper surface of the semiconductor test piece; S3: coating a polymer layer on the first platinum layer; The thickness of the polymer layer is 300-1000 nm; S4: preparing a second platinum layer on the upper surface of the polymer layer; A second platinum layer is prepared on the polymer layer using an electron beam in the FIB chamber; S5: preparing a third platinum layer on the upper surface of the second platinum layer; A third platinum layer is prepared on the second platinum layer using an ion beam in the FIB chamber.

[0006] Further, step S3 includes: S31: heating the polymer layer substrate; First, place the polymer layer substrate on a stirrer with a heating function and heat it to 50-60°C to improve fluidity; S32: adding additives to the polymer layer substrate and stirring evenly to obtain a polymer layer coating; S33: coating with polymer layer; The prepared polymer layer coating is coated on the upper surface of the prepared first platinum layer. After coating, the coating is allowed to stand at room temperature for 30-50 minutes to ensure that the polymer layer coating forms a film.

[0007] Furthermore, the polymer layer substrate includes but is not limited to polyacetylene, polypyrrole, polythiophene, polyaniline, polyparaphenylene, and polyparaphenylene vinylene; The additives include but are not limited to graphite, carbon black, carbon fiber, carbon nanotubes, and metal powder; the metal powder includes copper powder and nickel powder.

[0008] Furthermore, in the polymer layer coating, the ratio of polymer layer substrate to additive is 100:1-3 by weight.

[0009] Furthermore, the thickness of the first platinum layer is 5-10 nm; the thickness of the second gold layer is 50-100 nm; and the thickness of the third platinum layer is 500-1000 nm.

[0010] Furthermore, the thickness of the polymer layer is 300-500 nm.

[0011] Furthermore, the semiconductor test piece includes a compound semiconductor or a solar cell; the compound semiconductor includes multiple types of light-emitting diodes, and the light-emitting diodes include InGaN and InGaP; the solar cell includes copper, indium, gallium, and selenium.

[0012] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention adds a layer of polymer material with better thermal conductivity between the first and second platinum layers above the target area, so that the heat accumulated during FIB cutting analysis can be effectively conducted out of the target area, reducing the chance of low-melting-point metal migrating outward. The working process is to first sputter a first platinum layer on the surface of the test piece, and then prepare the polymer material on the test piece by coating. Then, in the FIB cavity, the second and third platinum layers are prepared above the analysis target area by electron beam and ion beam respectively, completing the test piece preparation work before FIB cutting analysis. In addition to being able to effectively conduct heat out of the target area, the selection of polymer materials with better thermal conductivity has three major advantages. First, it is easy to prepare, and can be implemented at room temperature by simple coating. Second, the polymer material does not react with the constituent elements in the test piece. Third, because of this layer of polymer material, the damage and knife mark effect of the test piece caused by high-energy ion beam bombardment can be reduced. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 It is a schematic diagram of the cross-sectional structure of the test piece prepared before FIB cutting analysis using the conventional method of the present invention; Figure 2 A flowchart of the steps of the preparation method for FIB analysis of cross-sections of low-melting-point materials improved by the present invention; Figure 3 The schematic diagram of the cross-sectional structure of a semiconductor test piece after preparation is an improved preparation method suitable for FIB analysis of cross-sectional low-melting-point materials according to the present invention. DETAILED DESCRIPTION

[0014] In order to provide a further understanding of the purpose, structure, features, and functions of the present invention, the following detailed description is given in conjunction with the embodiments.

[0015] like Figure 2 , an improved preparation method suitable for FIB analysis of cross-section of low melting point materials, comprising the following steps: S1: prepare a semiconductor test piece; The semiconductor test piece may be a compound semiconductor or a solar cell, wherein the compound semiconductor includes a light emitting diode such as InGaN, InGaP, etc., and the solar cell includes a metal such as copper indium gallium selenide; the semiconductor test piece includes a target area; S2: sputtering a first platinum layer on the semiconductor test piece; A first platinum layer is prepared on the upper surface of the semiconductor test piece by using a sputtering machine, such as Figure 3 The first platinum layer is 5-10 nm thick and is used to protect the surface of the semiconductor test piece and prevent the ion beam from damaging the surface during the etching process. It also prevents the surface from being damaged by heat or chemical reactions, and also prevents the surface of the semiconductor test piece from being oxidized or contaminated by the outside world.

[0016] S3: coating a polymer layer on the first platinum layer; A polymer layer is prepared on the first platinum layer by coating, such as Figure 3 , the thickness of the polymer layer is 300-500 nm; while ensuring that the heat accumulated in the target area can be quickly and efficiently conducted away, it also reduces the FIB analysis cavity cutting time and improves analysis efficiency.

[0017] S31: heating the polymer layer substrate; First, place the polymer layer substrate on a stirrer with a heating function and heat it to 50-60°C to improve its fluidity; The polymer layer substrate includes polyacetylene (PA), heterocyclic polymers: polypyrrole (PPy), polythiophene (PT), aromatic polymers: polyaniline (PAn), poly(p-phenylene) (PPP), polymers containing unsaturated hydrocarbons and aromatics: poly(phenylene vinylene) (PPV), etc. Polyacetylene is a conjugated polymer with an alternating single and double bond (C=C) structure, which makes it have good conductivity and enables electrons to propagate effectively, thereby promoting heat transfer to a certain extent. It has strong chemical stability, fewer reactive functional groups and relatively low electron carrier concentration, so that polyacetylene does not react with the elements in the semiconductor test piece when it comes into contact with the test piece.

[0018] Polypyrrole (PPy) is a conductive polymer with good electrical conductivity, which is usually used in electrochemistry, batteries, sensors, supercapacitors and other applications. In its basic form, the thermal conductivity is not particularly high. This is because its molecular structure is relatively loose and lacks a regular lattice structure like metals or certain crystalline materials. By doping or compounding with other high thermal conductivity materials (such as graphene, carbon nanotubes, etc.), the thermal conductivity is increased, which facilitates the preparation of high thermal conductivity materials, and the performance is stable and will not react with semiconductor test pieces.

[0019] Polythiophene (PT) has high electrical conductivity, stable chemical properties, and is resistant to oxidation and other environmental factors to a certain extent. It will not react with the elements in the test piece, has good processability, and has good solubility. It can be processed into thin films, coatings, etc. through solutions for various electronic applications. It is easy to use and combines polythiophene with high thermal conductivity materials (such as graphite, carbon nanotubes, etc.) to improve the overall thermal conductivity and is easy to use.

[0020] Polyaniline has excellent electrical conductivity and adjustable electrical properties, has strong adjustability, is easy to add high thermal conductivity additives to improve thermal conductivity, and is easy to use. It has good chemical and thermal stability and does not react with elements in semiconductor test pieces.

[0021] Poly(p-phenylene) (PPP) has excellent electrical conductivity, good air stability and heat resistance, low raw material price, easy to make into soft and tough films, and can be solution and melt processed, which is conducive to the combination of additives to form thermal conductive materials, easy to use and convenient to coat.

[0022] Poly (phenylene vinylene) (PPV) is a conductive polymer material with good solubility and processability. It can be processed into a thin film by solution method, spraying method or spin coating method, and is convenient for coating to form a polymer layer.

[0023] S32: adding additives to the polymer layer substrate and stirring evenly; The additive is mixed into the heated polymer layer substrate in a ratio of 100:1-3 by weight and stirred evenly with a stirrer; ensuring that the additive can be evenly distributed in the polymer material, and after stirring evenly, heating and stirring to obtain a polymer layer coating; The additives include graphite, carbon black, carbon fiber, carbon nanotubes, various metal powders, such as copper powder, nickel powder, etc.; Graphite has a very high thermal conductivity, especially in the direction parallel to the plane. As an additive, it significantly improves the thermal conductivity of the material, reduces thermal dissipation, and facilitates heat dissipation.

[0024] Carbon black has a high specific surface area, provides strong electrical conductivity, has good dispersibility, can be evenly distributed in the polymer layer substrate, improves strength and toughness, has good fire resistance, and ensures good flame retardancy of the polymer layer.

[0025] Carbon fiber has a very low density, good conductivity, and good corrosion resistance. When used as an additive, it can significantly improve the mechanical properties of the matrix material and enhance the strength, rigidity, and impact resistance of the composite material.

[0026] Carbon nanotubes have very high thermal conductivity, especially along their axial direction, which improves the thermal conductivity of the material. They also have excellent dispersibility and enhancement effects when used in polymer material layers, and can significantly improve the performance of the material at very low addition amounts.

[0027] Copper powder: Copper is a very good thermal conductor, so copper powder can significantly improve the thermal conductivity of the polymer layer substrate; Nickel powder effectively improves thermal conductivity, electrical conductivity, enhances mechanical properties, and resists oxidation and corrosion.

[0028] Adding additives to the polymer layer substrate can improve the performance of the polymer substrate, enhance the thermal conductivity of the substrate, improve heat dissipation efficiency, and reduce local overheating; thermally conductive polymer materials can quickly conduct heat from the heat source area to other areas or heat sinks, thereby reducing the temperature, avoiding heat accumulation, preventing atomic migration caused by high temperature, and reducing the risk of material failure.

[0029] S33: coating with polymer layer; The prepared polymer layer coating is applied on the upper surface of the first platinum layer. After coating, it is left to stand at room temperature for 30-50 minutes to ensure that the polymer layer coating forms a film. The thickness of the polymer layer must be more than 300 nm so that the heat accumulated in the target area can be quickly and efficiently guided out. In order to reduce the FIB cutting time and efficiency, the thickness of the polymer layer must be less than 1000nm. The polymer layer with more additives can effectively guide the heat accumulated by FIB cutting away from the target area, so that the low-melting-point metal will not migrate, and effectively reduce the damage and knife mark effect of the test piece caused by the bombardment of the high-energy ion beam during the cutting process.

[0030] S4: preparing a second platinum layer on the upper surface of the polymer layer; A second platinum layer is prepared on the polymer layer using an electron beam in the FIB chamber, such as Figure 3 , the thickness of the second platinum layer is 50-100 nm. The second platinum layer protects the polymer layer, reduces the risk of surface oxidation or material degradation of the polymer layer of the semiconductor test piece, reduces physical damage to the surface, and avoids subsequent operations affecting the polymer layer. At the same time, the thickness is moderate, which is convenient for subsequent analysis or sample processing. The platinum layer can be removed relatively easily, especially through the scanning of the FIB ion beam, which can accurately remove the protective layer, improve FIB cutting efficiency, and reduce cutting time.

[0031] S5: preparing a third platinum layer on the upper surface of the second platinum layer; A third platinum layer is prepared on the second platinum layer using an ion beam in the FIB chamber, such as Figure 3 The thickness of the third platinum layer is 500-1000 nm. The specimen preparation before FIB cutting analysis is completed. The third platinum layer enhances stability and etching resistance, maintaining the stability of the semiconductor specimen structure. Ensure that the microstructure of the semiconductor will not be excessively affected or damaged by the ion beam during cutting.

[0032] The present invention adds a polymer layer with better thermal conductivity between the first and second platinum layers above the target area, so that the heat accumulated during FIB cutting analysis can be effectively conducted out of the target area, reducing the chance of low melting point metal migrating outward.

[0033] Because the atoms in the solid will vibrate at the lattice equilibrium position due to the temperature, when the ambient temperature increases, the atoms absorb more energy and increase the vibration, and the atoms are more likely to break free and jump out of the original equilibrium position, which is called atomic migration. When a large number of atoms migrate, a large amount of material will flow, causing the internal morphology of the solid to change. The factors that affect atomic migration are mainly temperature. The higher the temperature, the more obvious the migration phenomenon. The melting point of the material is also related to the degree of migration. The lower the melting point, the more easily the atoms are affected by temperature and migrate. Conversely, for materials with high melting points, higher temperatures are required to cause obvious migration. During the FIB cutting process, the collision between high-energy ions and atoms causes the local temperature to rise. If the material contains low-melting-point atoms, it is very common to produce the effect of atomic migration due to the temperature increase. The present invention adds a polymer layer to the traditional method, which has three main advantages. First, it provides a heat dissipation channel to effectively transfer the heat generated during FIB cutting to the base carrying the test piece, so that the temperature in the target area is maintained below 50°C. Second, this polymer layer is easier to prepare than the platinum layer prepared in FIB. It can be prepared on the test piece by coating. Third, the temperature for preparing the polymer layer is room temperature, and there is no interference from any electron beam or ion beam, which ensures that the sample remains original.

[0034] The present invention has been described by the above-mentioned relevant embodiments, however, the above-mentioned embodiments are only examples for implementing the present invention. It must be pointed out that the disclosed embodiments do not limit the scope of the present invention. On the contrary, changes and modifications made without departing from the spirit and scope of the present invention are all within the scope of patent protection of the present invention.

Claims

1. An improved preparation method suitable for FIB analysis of cross-sections of low-melting-point materials, characterized in that: The following steps are involved: S1: prepare a semiconductor test piece; The semiconductor test piece includes a target area; S2: sputtering a first platinum layer on the upper surface of the semiconductor test piece; S3: coating a polymer layer on the first platinum layer; The thickness of the polymer layer is 300-1000 nm; S4: preparing a second platinum layer on the upper surface of the polymer layer; A second platinum layer is prepared on the polymer layer using an electron beam in the FIB chamber; S5: preparing a third platinum layer on the upper surface of the second platinum layer; A third platinum layer is prepared on the second platinum layer using an ion beam in the FIB chamber.

2. The improved preparation method for FIB analysis of cross-section of low melting point materials as claimed in claim 1, characterized in that: Step S3 includes: S31: heating the polymer layer substrate; First, place the polymer layer substrate on a stirrer with a heating function and heat it to 50-60°C to improve fluidity; S32: adding additives to the polymer layer substrate and stirring evenly to obtain a polymer layer coating; S33: coating with polymer layer; The prepared polymer layer coating is coated on the upper surface of the prepared first platinum layer. After coating, the coating is allowed to stand at room temperature for 30-50 minutes to ensure that the polymer layer coating forms a film.

3. The improved preparation method suitable for FIB analysis of cross-section of low melting point materials as claimed in claim 2, characterized in that: The polymer layer substrate includes but is not limited to polyacetylene, polypyrrole, polythiophene, polyaniline, polyparaphenylene, and polyparaphenylene vinylene; The additives include but are not limited to graphite, carbon black, carbon fiber, carbon nanotubes, and metal powder; the metal powder includes copper powder and nickel powder.

4. The improved preparation method for cross-section FIB analysis of low melting point materials as claimed in claim 2, characterized in that: In the polymer layer coating, the ratio of polymer layer substrate to additive is 100:1-3 by weight.

5. The improved preparation method suitable for FIB analysis of cross-section of low melting point materials as claimed in claim 1, characterized in that: The thickness of the first platinum layer is 5-10 nm; the thickness of the second gold layer is 50-100 nm; and the thickness of the third platinum layer is 500-1000 nm.

6. The improved preparation method for cross-section FIB analysis of low melting point materials as claimed in claim 1, characterized in that: The thickness of the polymer layer is 300-500 nm.

7. The improved preparation method for cross-section FIB analysis of low melting point materials as claimed in claim 1, characterized in that: The semiconductor test piece includes a compound semiconductor or a solar cell; the compound semiconductor includes multiple types of light emitting diodes, and the light emitting diodes include InGaN and InGaP; the solar cell includes copper, indium, gallium, and selenium.

Citation Information

Cited By

  • Test piece protection method for preventing damage caused by laser bombardment

    CN120927718A